Production and acceptance evaluation of Fresh ricotta prepared with functional foods (Research, Society and Development, 2020)
Ricotta is a cheese widely consumed in diets because its high nutritional value, high protein content and for being low fat. In addition, it has an important environmental role looking at the non-disposal of the serum resulting from cheese produced by the industries. Considering this factor, and linking it to a relevant functional aspect capable of generating even more health benefits, the project aimed to manufacture two types of functional ricotta, one with chia and the other with flaxseed. In order to assess the acceptability of the products, sensory analyzes were carried out covering the parameters of appearance, taste, odor and texture, in addition to evaluating the purchase intention, the ricotta yield and pH analyzes with 1, 7, 14 and 21 days. The purchase intention of the ricotta with chia was 87.5%, and the purchase intention of the ricotta with flaxseed was 90% when considering the purchase intention of the forty voting analysts. Both had a good yield and pH variations within the expected over the days. By the evaluations, such products demonstrate the possibility of innovation in the dairy sector and present themselves as an incipient proposal in the research and development of new products and in future academic research.